Indonesian Dentists' Perception of the Use of Teledentistry - Anandina Irmagita Soegyanto; Yuniardini Septorini Wimardhani; Diah Ayu Maharani; Marc Tennant (Elsevier, 2022)
Introduction: Teledentistry is the use of information and communication technology to provide dental services from distant locations. The use of teledentistry is highly beneficial in the COVID-19 pandemic era. Objective: This study aimed to explore Indonesian dentists' perceptions of the use of teledentistry in their daily practice and the benefits for patients. Methods: This was a descriptive cross-sectional study comprising an electronic survey of Indonesian dentists. We used a cross-cultural, adapted questionnaire that consisted of 26 items and 5-point Likert scale questions that evaluated dentist perception in the following 4 domains: usefulness of teledentistry for dental practice, usefulness of teledentistry to improve practices, usefulness of teledentistry for patients, and dentists who had concerns about the use of teledentistry. Results: A total of 652 dentists from 34 provinces in Indonesia participated in this study. The majority of respondents agreed about the usefulness of teledentistry in dental practice, especially for saving time, compared to referral letters (87%). Most respondents recognised the utility of teledentistry for improving dental practice and its benefits for patients. Nevertheless, most of the dentists had concerns about teledentistry in terms of digital forgery concern (74.2%) and technical incompatibility (71.8%). Conclusions: Indonesian dentists reported their positive perception of the usefulness of teledentistry for improving dental practice and benefits for patients, although some concerns were still present. Further studies on the application of teledentistry in Indonesia are still needed.